Incidence, nature and mortality of cytomegalovirus infection after double-unit cord blood transplant. Issue 6 (June 2015) - Dahi, Parastoo B.; Perales, Miguel A.; Devlin, Sean M.; Olson, Amanda; Lubin, Marissa; Gonzales, Anne Marie; Scaradavou, Andromachi; Kernan, Nancy A.; O'Reilly, Richard J.; Giralt, Sergio; Jakubowski, Ann; Koehne, Guenther; et al.
Abstract Cord blood transplant (CBT) extends allograft access but is associated with a significant risk for cytomegalovirus (CMV) infection. We analyzed CMV infection in 157 CBT recipients transplanted for hematological malignancies. As compared with antigenemia testing, routine polymerase chain reaction (PCR) monitoring was associated with increased and earlier CMV infection detection (1-year incidence if seropositive 67% [median onset 41 days] vs. 100% at an earlier 33-day median [p < 0.001]) and decreased gastrointestinal disease. One-year CMV-related transplant-related mortality was 11% in CMV+ patients with 7/9 deaths associated with initial infection. Disease-free survival was lower in seropositive compared with seronegative patients (1-year: 55% vs. 73%, p = 0.02). However, in multivariate analysis adjusting for age, treatment failure risk in CMV+ patients was not significant (hazard ratio 1.52, p = 0.11). CMV infection is a major challenge in seropositive CBT recipients. While PCR surveillance permits early detection of viremia, new prophylaxis and therapeutic strategies are needed.